Proteolytic Modulation of Thrombopoietin Activity: Comparison of Thrombin, Plasmin, and Urokinase - Reiner, Alexander P.; Aramaki, Kaelen M. (Thrombosis and Haemostasis, 2000)
Several observations suggest that limited proteolysis of full-length 70 kD human thrombopoietin (Tpo) may be important for Tpo biology. Recently, it was reported that thrombin cleaves full-length recombinant human Tpo (rhTpo) sequentially at two sites, Arg195 within the glycan domain followed by Arg117 within the cytokine domain, and that these cleavages modulate Tpo activity in vitro. We demonstrate that urokinase and plasmin also cleave rhTpo in a time-dependent manner. Urokinase cleavage is confined to the glycan domain, and generates a 35 kD N-terminal fragment that contains the intact cytokine domain, and is associated with increased Tpo activity. In contrast, plasmin cleaves Tpo sequentially at two specific sites (Arg205 within the glycan domain followed by Lys52 within the cytokine domain), and is associated with a marked decrease in Tpo activity. These proteolytic events have potential implications for regulation of Tpo activity in vivo.
Keywords: Thrombopoietin; urokinase; plasmin; thrombin; Mpl